Роман Л. Толстого “Воскресіння” і повість В. Винниченка “Краса і сила”: міжтекстові перегуки й особливості індивідуального художнього мислення - Брайко, О. (Слово і Час, 2018)
У статті вказано на перегуки між дебютним твором українського прозаїка і драматурга (1902) і
романом Л. Толстого, опублікованим незадовго перед тим (1899). Розглянуто супутні обставини,
які могли спонукати початківця зацікавитися популярним твором. Проаналізовано образотворчі
подібності, композиційні збіги й можливі алюзії Винниченка до роману і Євангелія. Елементи в
характеристиці персонажів-в'язнів, які у Л. Толстого акцентують психологічну багатогранність
постатей, у Винниченка набувають самодостатньої ваги як майже пародійні щодо високого
літературного зразка чи навіть шаржовані засоби образотворення. Відмінність Винниченкового
типажу й художніх засобів від постатей і стилю роману Толстого за доволі виразного тематичного
перегуку засвідчує оригінальність автора-початківця, спроможність подати українську версію
актуального соціально-аналітичного художнього дискурсу. Епізод “Краси і сили” своїми
культурними кодами, портретними штрихами, розвитком дії (переходом догматичного діалогу в
полілог) резонує з розлогою епічною структурою “Воскресіння” й водночас заперечує її в манері
зображення – демонстративній простоті й позірній поверховості змісту. The paper indicates correspondences in the debut work of the Ukrainian prose writer and playwright
V. Vynnychenko (written in 1902) and the novel by Lev Tolstoy, published a bit earlier (1899). It offers an
analysis of attendant circumstances which could induce a beginner to become interested in the popular
work. It is proved that V. Vynnychenko could be acquainted with the complete version of the classic
text. The researcher pays attention to similarity of psychological models and polylogue remarks (in the
scenes of discussions) in the story by V. Vynnychenko to the corresponding means in two episodes of
Tolstoy’s novel and the Russian writer’s detailed narrative retrospective view (psychological portraits
of secondary characters). At the same time it’s difficult to reconstruct the particular correspondences
and allusions in the story of the Ukrainian author due to different plot and social groups depicted.
The works by Vynnychenko and Tolstoy have such common genre and composition elements as
ideological discussion, intentional relation to eventual social and eschatological revelation (in the novel)
or the sacral practice of ‘live’ faith, unusual form of religious experience, in contrast to the worn ritual (in
the story). In the structure of the novel the existential variations of answers to the ‘general questions’
get comprehensive psychological motivation, external evaluation and, after all, are indirectly projected
onto universal explanatory source, the Gospel. Vast epic action and its consistent intellectualisation
make the judgments of the narrator an authoritative interpretation of the portrayed figures. In V.
Vynnychenko’s story narrative remarks and information usually stay within comprehension limits
of imaginary external observers, so that a retrospective view doesn’t go further than the described
situation. The 3rd person narrator of all work is likened to the spectator and listener, never pretending
to be a qualified psychologist. The elements in description of one or another prisoner character,
emphasizing many-sided psychological nature of the characters and being most remarkable for the
readers of L. Tolstoy, in V. Vynnychenko’s story are intentionally made almost a parody in relation to
the high literary standard. В статье указано на переклички между журнальным
дебютом украинского прозаика и драматурга (1902)
и романом Л. Толстого, опубликованным в 1899 г.
Рассмотрены сопутствующие обстоятельства, которые
могли побудить начинающего прозаика заинтересоваться
популярным произведением. Проанализированы
изобразительные подобия, композиционные
совпадения и возможные аллюзии Винниченко к
роману и Евангелиям. Элементы в характеристике
персонажей-узников, которые у Л. Толстого акцентируют
психологическую многогранность фигур, у Винниченко
приобретают самодостаточный вес как почти пародийные
относительно высокого литературного образца или даже шаржированные средства создания образов.
Отличие типажа и художественных средств украинского автора от персонажей и стиля романа Толстого при
достаточно заметных тематических перекличках указывает на оригинальность дебютанта, способность
предложить украинскую версию актуального социально-аналитического художественного дискурса. Эпизод
“Красоты и силы” своими культурными кодами, портретными штрихами, развитием действия (переходом
догматического диалога в полилог) резонирует с широкой эпической структурой “Воскресения” и в то же время
отрицает ее в манере изображения – демонстративной простоте и внешней поверхностности содержания.